2002
DOI: 10.5858/2002-126-1394-hcid
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Cofactor II Deficiency

Abstract: Objectives.—To review of the state of the art relating to congenital heparin cofactor II deficiency as a potential risk factor for thrombosis, as reflected by the medical literature and the consensus opinion of recognized experts in the field, and to make recommendations for the use of laboratory assays for assessing this thrombotic risk in individual patients. Data Sources.—Review of the medical literature, primarily from the last 10 years. Data Extraction and Synthesis.—After an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 90 publications
0
13
0
1
Order By: Relevance
“…The DS−HCII system has a number of important physiological roles. HCII is a human plasma ser ine p roteinase in hibitor (serpin) that specifically inhibits thrombin, a key enzyme playing a critical role in hemostasis. The intrinsic specificity of HCII may be a unique advantage because its deficiency does not appear to enhance risk for thrombosis . At the same time, the serpin prevents arterial thrombosis. ,,, HCII is also able to inhibit clot-bound thrombin, in striking contrast to AT .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The DS−HCII system has a number of important physiological roles. HCII is a human plasma ser ine p roteinase in hibitor (serpin) that specifically inhibits thrombin, a key enzyme playing a critical role in hemostasis. The intrinsic specificity of HCII may be a unique advantage because its deficiency does not appear to enhance risk for thrombosis . At the same time, the serpin prevents arterial thrombosis. ,,, HCII is also able to inhibit clot-bound thrombin, in striking contrast to AT .…”
mentioning
confidence: 99%
“…The intrinsic specificity of HCII may be a unique advantage because its deficiency does not appear to enhance risk for thrombosis . At the same time, the serpin prevents arterial thrombosis. ,,, HCII is also able to inhibit clot-bound thrombin, in striking contrast to AT . Despite these advantages, no anticoagulant has yet been developed that utilizes the HCII-based indirect pathway of coagulation regulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…41 Heterozygous HCII deficiency has been reported to be associated with thromboembolic events, but some epidemiological studies suggested that heterozygous HCII deficiency is as common in healthy people as in patients with deep vein thrombosis (DVT). 42 The first subject with homozygous HCII deficiency had been reported for recurrent thrombosis, which was confirmed to be accompanied by ATIII deficiency. 43 A screening study of thromboembolic events in adolescents revealed two patients with HCII Rimini mutation, and they were proved to be complicated with FV Leiden mutation and type I PC deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Στις περισσότερες περιπτώσεις η ανεπάρκειά της κληρονοµείται µε τον αυτοσωµατικό επικρατούντα χαρακτήρα, µε επίπεδα παράγοντα 50% σε σχέση µε το γενικό πληθυσµό143 . Οι κλινικές εκδηλώσεις στα άτοµα που φέρουν τη διαταραχή ποικίλουν µεταξύ αρτηριακών και φλεβικών θροµβώσεων, ενώ αρκετοί φορείς παραµένουν ασυµπτωµατικοί144 .Για το λόγο αυτό η ανεπάρκεια HCII δεν θεωρείται σηµαντικός προθροµβωτικός παράγοτας, ενώ η επίπτωσή του σε άτοµα µε φλεβική θρόµβωση είναι 1% όσο και στο γενικό πληθυσµό141 .Πρόκειται για πρωτεΐνη του πλάσµατος η οποία δρα παρουσία του ενεργοποιηµένου παράγοντα X και αναστέλλει τη λειτουργία του συνδυασµού VIIa -ιστικού παράγοντα145 . Αυξηµένος κίνδυνος φλεβικής θρόµβωσης αναφέρεται βιβλιογραφικά από τη µετάλλαξη C356T στο γονίδιο TFPI146 , ωστόσο άλλες µελέτες δεν επιβεβαιώνουν τον ισχυρισµό αυτό147 .…”
unclassified